Mechanistic investigations of diabetic ocular surface diseases - Zhou, Qingjun; Yang, Lingling; Wang, Qun; Li, Ya; Wei, Chao; Xie, Lixin (Frontiers in Endocrinology, 2022)
Abstract: With the global prevalence of diabetes mellitus over recent decades, more patients suffered from various diabetic complications, including diabetic ocular surface diseases that may seriously affect the quality of life and even vision sight. The major diabetic ocular surface diseases include diabetic keratopathy and dry eye. Diabetic keratopathy is characterized with the delayed corneal epithelial wound healing, reduced corneal nerve density, reduced corneal sensation and feeling of burning or dryness. Diabetic dry eye is manifested as the reduction of tear secretion accompanied with the ocular discomfort. The early clinical symptoms include dry eye and corneal nerve degeneration, suggesting the early diagnosis should be focused on the examination of confocal microscopy and dry eye symptoms. The pathogenesis of diabetic keratopathy involves the accumulation of advanced glycation end-products, impaired neurotrophic innervations and limbal stem cell function, and dysregulated growth factor signaling, and inflammation alterations. Diabetic dry eye may be associated with the abnormal mitochondrial metabolism of lacrimal gland caused by the overactivation of sympathetic nervous system. Considering the important roles of the dense innervations in the homeostatic maintenance of cornea and lacrimal gland, further studies on the neuroepithelial and neuroimmune interactions will reveal the predominant pathogenic mechanisms and develop the targeting intervention strategies of diabetic ocular surface complications.